Digital Forensic Analysis of Telegram Messenger App in Android Virtual Environment - Raza, Ahmed; Bilal Hassan, Muhammad (Mobile and Forensics, 2022)
The paper provides an in-depth analysis of the artifacts generated by the Telegram Messenger application on Android OS which provides secure communications between individuals, groups, and channels. Since the past few years, the application went through major changes and updates and the latest version’s artifacts varied from the previous ones. Our methodology is based on the set of experiments designed to generate the artifacts from various use cases on the virtualized environment. The acquired artifacts such as messages, their location, and data structure how they relate to one another were studied and were then compared to the older versions. By correlating the artifacts of newer version with the older ones, it shows how the application have been upgraded behind the scenes and by incorporating those results can provide investigators better understanding and insight for the certain evidence in a potential cybercrime case.